Customizing egg incubators for Cameroon: A design and construction guide - Marck Jickel Kemegne Tagne; Thomas Kanaa; Paul Etouke Owoundi; Arnaud Obono Biyobo (PLoS ONE, 2025)
In Cameroon, poultry farming represents an important source of income for many families and is a key sector for economic development and food security. However, there is a deficiency in suitable infrastructure, especially high-performance and affordable incubators, leading many poultry farmers to resort to manual incubation techniques, which are often inefficient and labor-intensive. This paper aims to build an automatic incubator using locally accessible materials, optimized techniques, and modern, simple technologies. This paper also serves as a construction guide. Its initiative offers a significant opportunity to improve poultry farming practices, increase local productivity, and contribute to sustainable development. The incubator is built using the prototyping method, and the optimization of energy efficiency for the system was achieved through the mathematical modeling of heat transfer. The study’s findings indicate that the incubator is a dependable and effective solution for hatching poultry eggs. Its user-friendly design, ease of maintenance, and affordability make it an excellent choice for local poultry farmers.